Analisis Work–Life Balance Pekerja Perempuan dalam Konflik Peran Ganda: Studi Kasus PT Citra Tubindo Tbk - Lizania Syahputri; Ngaliman; Muammar Khaddafi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the work - life balance of female workers in work - family conflict (Case Study of PT Citra Tubindo Tbk). This study analyzes what work - family conflicts most often occur so that they can hinder the work - life balance of female workers and find out whether the support of women's empowerment organizations has been effective in helping female workers in dealing with work - family conflicts at PT Citra Tubindo Tbk and achieving work - life balance. This study uses primary data from structured in-depth interview techniques and direct observation. The sample determination in this study used cluster sampling technique so that the sample used was 16 female workers who worked in the RFPC department (Regional Finance and Procurement Center). The results of this study were analyzed using deductive thematic analysis techniques. The results showed that female workers at PT Citra Tubindo Tbk have succeeded in achieving work-life balance despite experiencing work - family conflict with organizational support that is considered effective in helping female workers. Most of female workers have achieved a balance of involvement (involvement balance) in work and family even though they experience conflicts of physical and psychological tension in family life caused by work life. This is due to the support of the Women@Vallourec organization which is considered the most effective in helping work - family conflict.